EKSISTENSI PEREMPUAN PADA LEMBAGA POLITIK FORMAL DALAM MEWUJUDKAN KESETARAAN GENDER (Studi Terhadap Anggota Legislatif di Provinsi Riau) - Jumni Nelli (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
The involvement of women in politics is important, because women have special needs that can only be understood best by the women themselves. If the women's problems is entrusted to the representatives who do not have the perspective of a female problem, it is almost certain that the policy issued is not sensitive to women's issues. Currently the representation of women is still low, not least in the province of Riau. But the low or lack of women's representation in the legislative agenda does not mean the strengthening of gender equality or gender mainstreaming (PUG) neglected. Interesting traced the existence of women legislators in Riau Province area totaling 18 people from 65 people to the Province, seven women sitting in Pekanbaru, and six women in Kampar truly representative of women in the province of Riau. The study concluded Women legislators in Riau Province is very sensitive and understand the problems and issues of gender/women, but because there is still minimal cause many obstacles encountered in achieving gender equality.